Investigating the Factor Structure of the Myers-Briggs Type Indicator (MBTI): Case of Indonesian Students - Nugraha, Dwi Yan; Widyastuti, Widyastuti; Ridfah, Ahmad (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
Psychological tests require continuous refinement and evaluation to ensure their effectiveness. This study aimed to evaluate the factor structure, invariance, item quality, and differential item functioning (DIF) of the 60-item Myers–Briggs Type Indicator (MBTI) among Indonesian students using modern psychometric methods. Involving 7,526 participants, the results of the item factor analysis (IFA) indicated that a single-factor model for each MBTI dimension adequately fit the data, supporting satisfactory construct validity. The Infit and Outfit MNSQ values ranged between 0.5 and 1.5, demonstrating good item quality. Moreover, no gender bias was detected based on the DIF Contrast effect size, indicating that MBTI items function equivalently for male and female students. These findings provide strong empirical evidence for the psychometric validity and reliability of the MBTI in the Indonesian context and represent the first large-scale study contributing to the refinement and modernization of the instrument in alignment with national legislative standards for psychological test use.